Expression of Agrobacterium Homolog Genes Encoding T-complex Recruiting Protein under Virulence Induction Conditions - Yang, Jing; Wu, Meixia; Zhang, Xin; Guo, Minliang; Huang, Zhiwei (Frontiers in Microbiology, 2015)
Proteins encoded by three Agrobacterial genes atu5117, atu4860 and atu4856 are highly homologous to each other in amino acid sequence. All three proteins are able to bind VirD2 and named as VBP1, VBP2 and VBP3 (VirD2-binding protein) respectively. VBP is involved in the T-DNA transfer by recruiting the T-complex to T4SS and defined as “T-complex recruiting protein”. To know whether these three homologous genes are expressed differently under virulence induction conditions, we tested the effects of virulence induction conditions, including varied pH, temperature and acetosyringone concentration, on the expressions of three VBP-encoding genes. Our data showed that atu5117 and atu4856 maintained constant expression under the tested induction conditions, whereas the expression of atu4860 was affected by the culture conditions. The culture conditions favorable to the expression of atu4860 differ from the reported induction conditions for other virulence proteins. Especially, pH value was a crucial factor for the expression of atu4860. Moreover, the deletion of atu5117 affected the expression of atu4860. These results suggest that the mechanisms regulating the expression of these three homologous genes are different from the virulence induction mechanism and that VBP homologs are presumably involved in other biological processes in addition to T-complex recruitment.